Morphology and distribution of ovipositor sensilla of female cotton leaf worm Spodoptera littoralis (Lepidoptera: Noctuidae), and evidence for gustatory function. Issue 1 (25th January 2016) - Seada, Mervat A.; Ignell, Rickard; Anderson, Peter
Abstract: The ovipositor of S podoptera littoralis has many sensilla, which implies a distinct sensory function of this organ in the assessment of the egg laying substrates and placement of eggs. The ovipositor is composed of two papillae densely packed with sensilla. Scanning electron microscopy showed that there are four categories of sensilla chaetica ( s. chaetica ), characterized based on differences in distribution, length and morphology, distributed on each papilla: Type I with 69 ± 2.9 sensilla on each papilla (length: 29–163 μm) distributed at the base; Type II with 19 ± 1.8 sensilla (length: 287–446 μm) distributed medially; Type III with 120 ± 7.8 sensilla (length: 62–156 μm) distributed distally; and Type IV 8 ± 0.9 sensilla (length: 72–91 μm) scattered between Type III sensilla. The structure of s. chaetica  Types I–III suggests a mechanosensory function, whereas electrophysiological analysis of s. chaetica  Type IV showed responses from four gustatory neurons and one mechanosensory neuron. Of the chemoreceptive neurons, one responded to salt, one to the secondary compound caffeine, one to sugars, mainly sucrose and fructose, and lastly one potentially to water. Behavioral studies are needed to verify the role of these sensilla during choice of oviposition site. Abstract : The ovipositor of Spodoptera littoralis is packed with many sensilla which imply a distinct sensory function of this organ in the assessment of the egg laying substrates. The structure of sensilla chaetica (s. chaetica) Types I–III suggests a mechanosensory function, whereas electrophysiological analysis of s. chaetica Type IV showed responses of at least four chemosensory neurons and one mechanosensory neuron.